Analysis of microsatellite instability in gastric mucosa-associated lymphoid tissue lymphoma. Issue 4 (April 2013) - Degroote, Annemarie; Knippenberg, Lies; Borght, Sara Vander; Spaepen, Marijke; Matthijs, Gert; Schaeffer, David F.; Owen, David A.; Libbrecht, Louis; Lambein, Kathleen; de Hertogh, Gert; Tousseyn, Thomas; Sagaert, Xavier
Abstract In Helicobacter pylori gastritis, constant antigenic stimulation triggers a sustained B-cell proliferation. Errors made during this continuous DNA replication are supposed to be corrected by the DNA mismatch repair mechanism. Failure of this mismatch repair mechanism has been described in hereditary non-polyposis colorectal cancer (HNPCC) and results in a replication error phenotype. Inherent to their instability during replication, microsatellites are the best markers of this replication error phenotype. We aimed to evaluate the role of defects in the DNA mismatch repair (MMR) mechanism and microsatellite instability (MSI) in relation to the most frequent genetic anomaly, translocation t(11;18)(q21;q21), in gastric mucosa-associated lymphoid tissue (MALT) lymphoma. Therefore, we examined 10 microsatellite loci (BAT25, BAT26, D5S346, D17S250, D2S123, TGFB, BAT40, D18S58, D17S787 and D18S69) for instability in 28 patients with MALT lymphomas. In addition, these tumors were also immunostained for MLH1, MSH2, MSH6 and PMS2, as well as screened for the presence of t(11;18)(q21;q21) by real-time polymerase chain reaction (RT-PCR). We found MSI in 5/28 (18%) lymphomas, with MSI occurring in both t(11;18)(q21;q21)-positive and -negative tumors. One tumor displayed high levels of instability, and, remarkably, this was the only case displaying features of a diffuse large B-cell lymphoma. All microsatellite unstable lymphomas showed a loss of MSH6 expression. In conclusion, our data suggest that a MMR-defect may be involved in the development of gastric MALT lymphomas, and that a defect of MSH6 might be associated with those MSI-driven gastric lymphomas.